THE EFFECT OF GROSS DOMESTIC PRODUCT, INTERNASIONAL CPO PRICE, CPO CONSUMPTION, AND INFLATION ON INDONESIA’S CRUDEPALM OIL EXPORT VOLUME - Nano Prawoto; Putriku Gusnia (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Palm oil is one of the non-oil and gas export commodities from plantation products. Crude palm oil (CPO) has been recognized as one of the main agricultural commodities for Indonesia's exports. Indonesia is the largest producer of palm oil, which makes exports as one of the sectors that can advance the Indonesian economy. This study aims to analyse Indonesian palm oil exports to 10 main export destination countries, including the Gross Domestic Product of destination countries, international CPO prices, destination country CPO consumption, and destination country inflation. The data used in this study is secondary data for 2018-2022 and is quantitative data. Panel data regression method was used in this research, with test results showing that the right model used is a fixed effect model. The results of this study show that the Gross Domestic Product and inflation of destination countries have a significant negative influence. Meanwhile, international CPO prices and CPO consumption of destination countries have a significant positive influence on the volume of Indonesian palm oil exports to the 10 main destination countries in 2018-2022. This research can be a reference related to Indonesia's palm oil export policy.